Aktivitas Sitotoksik Ekstrak Etanol, Fraksi Etanol, Etil-Asetat, dan Heksana Kulit Jeruk Purut (Citrus hystrix DC.) terhadap Sel Kanker Payudara T47D - Nabilla, Isya Isma; Indrayudha, Peni (Pharmacon: Jurnal Farmasi Indonesia, 2019)
Kaffir lime peels (Citrus hystric DC.) have been reported that it has activity on HeLa cell. The purpose of this study was to determine the cytotoxic activity of ethanol extract, ethanolic, ethyl acetate, and hexane fraction of kaffir lime peels to T47D breast cancer cells and to identify the compounds of kaffir lime peels (Citus hystrix DC.). Extraction was done by maceration using 96% ethanol. The results of thick extracts were fractionated by the liquid-liquid partition method using solvent with different polarity, namely hexane, ethyl acetate, and ethanol. Cytotoxic activity tests were carried out using the MTT assay. Identification of compounds were carried out by Thin Layer Chromatography (TLC) method with silica gel GF 254 as a stationary phase. The mobile phase used was hexane:ethylacetate (6:4) for ethanol extract, ethyl acetate and hexane fractions, and hexane:ethylacetate (4:6) for ethanol fractions. IC50 ethanol extract, ethyl acetate and hexane fractions obtained were 268.49, 286.82, and 136.27 mg/mL respectively. Ethanol extract, ethyl acetate, and hexane fractions contain alkaloid, flavonoid, terpenoid and phenolic compounds, while the ethanol fraction contains only flavonoid compound. Cytotoxic results of ethanol extract, ethanol, ethyl acetate, and hexane fraction of kaffir lime peels did not active against T47D breast cancer cells.